Lawmaking for Development. Explorations into the Theory and Practice of International Legislative Projects - Otto, J.M (Law, Governance, and Development, 2008)
This volume discusses how legislation (the product) and lawmaking (the process) function in developing countries, and how legislation contributes to development and how lawmaking and legislation can be improved either by the country itself or by donor assisted projects. It covers topics including legal transplantation, legislative quality, linkages between legislation and implementation, and the politics of lawmaking.